Magnetic NiFe2O4 Nanoparticles Prepared via Non‐Aqueous Microwave‐Assisted Synthesis for Application in Electrocatalytic Water Oxidation. Issue 68 (4th August 2021) - Simon, Christopher; Zakaria, Mohamed Barakat; Kurz, Hannah; Tetzlaff, David; Blösser, André; Weiss, Morten; Timm, Jana; Weber, Birgit; Apfel, Ulf‐Peter; Marschall, Roland
Abstract: Phase‐pure spinel‐type magnetic nickel ferrite (NiFe2 O4 ) nanocrystals in the size range of 4 to 11 nm were successfully synthesized by a fast and energy‐saving microwave‐assisted approach. Size and accessible surface areas can be tuned precisely by the reaction parameters. Our results highlight the correlation between size, degree of inversion, and magnetic characteristics of NiFe2 O4 nanoparticles, which enables fine‐tuning of these parameters for a particular application without changing the elemental composition. Moreover, the application potential of the synthesized powders for the electrocatalytic oxygen evolution reaction in alkaline media was demonstrated, showing that a low degree of inversion is beneficial for the overall performance. The most active sample reaches an overpotential of 380 mV for water oxidation at 10 mA cm −2 and 38.8 mA cm −2 at 1.7 V vs. RHE, combined with a low Tafel slope of 63 mV dec −1 . Abstract : Phase‐pure spinel‐type magnetic nickel ferrite (NiFe2 O4 ) nanocrystals in the size range of 4 to 11 nm were successfully synthesized by a fast and energy saving microwave‐assisted approach. Interestingly, a low degree of inversion is beneficial for the activity in electrocatalytic oxygen evolution.